Investigation of the Relationship between Air Pollution and Respiratory Health Outcomes in Pakistan - Imtiaz, Fazeela; Asghar, Anam; Asghar, Anfal; Noreen, Atika; Batool, Rida; Murtza, Muhammad; Attiq-Ur-Rehman (Indus Journal of Bioscience Research, 2024)
In developing countries such as Pakistan, the problem of air pollution is growing as industrialization, urbanization and limited environment regulations make its way to deteriorating air quality. The relationship between air pollution and respiratory health outcomes in Pakistan is investigated using epidemiological data, air quality indices and hospital admissions for respiratory diseases. Air pollution has become a major public health problem in Pakistan — due to urbanization, industrial expansion and population growth — the findings show, calling for targeted interventions and policy to mitigate the negative impact of air pollution on public health. This study explores spatial interconnections between air pollution and respiratory health outcomes across variable geographic regions of Pakistan. The study analyzes the impact of particulate matter (PM2.5 and PM10), nitrogen oxides (NOx), sulfur dioxide (SO₂), and carbon monoxide (CO) on asthma, chronic obstructive pulmonary disease (COPD) and acute respiratory infections by using analysis of air quality data and respiratory health statistics. The research finds that urban centers like Lahore, Karachi and Islamabad often have air pollution levels well above World Health Organization (WHO) guidelines, which goes hand in hand with an increase in incidence of respiratory illnesses. Health burden is made worse by seasonal variations, socio economic inequalities and restricted access to healthcare, especially among vulnerable groups including children and elderly people as well as low income populations. Air quality management as an urgent policy, urban planning as a sustainable planning and public health as the intervention measures should be implemented to prevent further air pollution impact on respiratory health, as revealed in this study. The research provides localized evidence to inform local policymakers and stakeholders and support collaborative efforts to better advance and monitor air quality and public health interventions in Pakistan.